2019
DOI: 10.1177/0143624419844753
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impacts of a changing climate on the risk of overheating and energy performance for a UK retirement village adapted to the nZEB standards

Abstract: The death toll of the 2003 heat wave in Europe exceeded 35,000 heat-related deaths. The elderly population were the most affected. The current paradigm within the construction industry in cold-dominant countries is to design/retrofit buildings with high levels of insulation. Whilst thermal comfort may be reached during colder months with this approach, the risk of overheating can be increased during hotter months. This paper aims to examine the impacts of a changing climate on the risk of overheating and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They recommended that the interrelationship between glazing, shading, and ventilation (amongst other variables) need to be collectively evaluated at the planning stage to ensure the appropriate design of an effective management strategy. Salem et al [4] carried out the investigation on the impacts of a changing climate on the overheating risk and energy performance for a village in United Kingdom (UK) adapted to the nZEB standards. They found that the buildings would most likely experience severe overheating after retrofitting.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended that the interrelationship between glazing, shading, and ventilation (amongst other variables) need to be collectively evaluated at the planning stage to ensure the appropriate design of an effective management strategy. Salem et al [4] carried out the investigation on the impacts of a changing climate on the overheating risk and energy performance for a village in United Kingdom (UK) adapted to the nZEB standards. They found that the buildings would most likely experience severe overheating after retrofitting.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of "near zero-energy buildings" (NZEBs) by the Energy Performance Building Directive (EPBD) (recast) in 2010 and the 2050 carbon budget, which led to a shift in the design paradigms within the construction industry across Europe, means that new and existing buildings are expected to be energy efficient [3][4][5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The basic concept behind the NZEB standard exacerbates the risk of overheating in homes under hotter weather conditions. Despite this, there is very little research and investigation regarding the issue and the potential of the wide-spread implementation of NZEB standards across Europe to compound the risk of overheating in buildings [3,6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Canada aims to reduce 50% of greenhouse gas emissions through building energy savings and green roof applications by the end of 2030 [6]. In order to respond to these policies and regulations related to zero-energy building, many studies have been conducted to estimate the effect of zero energy building constructions to the whole building stock and global climatic conditions [7][8][9]. Salem investigated the impact of zero energy building constructions on the built environment through simulations of zero-energy building standards to existing UK commercial and residential buildings [8].…”
Section: Introductionmentioning
confidence: 99%